AN HISTORICAL LOOK AT GEOMORPHOLOGY AND ITS ROLE AS AN APPLIED SCIENCE IN THE CONTEXT OF NATURAL HAZARDS AND LAND USE PLANNING - Arroyo-González, Luis Nelson (Revista Geográfica de América Central., 2012)
This article takes into consideration the historical antecedents that have contributed to the emergence of geomorphology as a science. Approaches and perspectives of some authors are inserted as a way to comment on the more relevant stages in this epistemological approach to natural hazards and their application in land use planning.